Psychological consequences of war as a real threat to young people with post-traumatic stress disorder - Chorna, Valentyna; Antomonov, Mykhailo; Syrota, Hanna; Syrota, Mariia; Kolomiets, Viktoria; Pavlenko, Nataliia (Rzeszów University Press, 2025)
Introduction and aim. The consequences of Russia’s invasion of Ukraine have led to a violation of the mental health of youth, children, and adults in Ukraine. Increased cases of mental disorders related to war trauma, including post-traumatic stress disorder (PTSD) due to violence, loss of family and friends, loss of normal life, fear, uncertainty, and constant stress, are leading to long-term PTSD, which can negatively affect their quality of life, such as physical, mental, and social well-being. Determination of symptoms of PTSD in students (men and women) of medical and technical higher education institutions during the war in Ukraine. Material and methods. At the beginning of 2024, the survey was attended by 452 students of Ukrainian higher education in stitutions (medical and technical), of which 24.6% were male and 75.4% were female, aged 15–19 (65.8%), aged 20–28 (21.1%), and over 29 (13.1%). The methodology ‘Identification of potentially traumatic events in life among applicants’ was used to iden tify students with signs of PTSD out of a total of 452 surveyed students. The next step was to assess the degree of PTSD symp toms in 121 students of the total number of students who were identified as having PTSD symptoms using the ‘PTSD symptoms list’. Research was conducted with the help of the STATISTICS program, by the Pearson’s Chi-square method, Spearman’s rank correlation coefficient (rS ). Results. The severity of the consequences of the war was assessed based on the results of a survey among students of high er education institutions during the hostilities in Ukraine. Students who participated in hostilities or were in the war zone represented 45.9% of respondents from technical universities (TU) and 24.8% of the respondents from medical universities (MU). Students who experienced sexual violence (rape, attempted rape, coercion to perform any type of sexual act by force or threats) made up 18.9% of the students in the TU and 16.9% in the MU. Conclusion. Sexual violence (rape, attempted rape, coercion to perform any type of sexual act by force or threats) among students in higher education institutions was experienced by 18.9% of respondents of technical specialization and 16.9% of respondents of medical specialization. The identified unfavorable features of students’ mental health during hostilities may lead to long-term negative consequences in the future. Particular attention should be paid to risk groups, including female students.
All subjects gave informed consent to the inclusion prior to participating in the study. The study has been approved by the Bioethics Committee at the University No 2023/09/01.
Keywords: Full-scale war; posttraumatic stress disorder; students of higher education institutions of technical and medical profile